PEMBELAJARAN FLIPPED CLASSROOM BERBANTUAN EDMODO UNTUK MENINGKATKAN MINAT DAN HASIL BELAJAR SISWA PADA MATERI PYTHAGORAS - Farman Farman; Chairuddin Chairuddin (Universitas Muhammadiyah Semarang, 2020)
This qualitative research aims to describe the students' interests and learning outcomes by learning a flipped classroom assisted by Edmodo on Pythagorean material. This research was conducted at SMP Mu'adz Bin Jabal Kendari in 2020 for grade VIIIB students, totaling 31 students. Learning interest data is obtained through a learning interest questionnaire, and learning outcome test data is obtained through a learning outcome test with the Edmodo application. The data analysis technique of this research includes data reduction, data presentation, and conclusion/verification. The results showed that Edmodo's flipped classroom had improved learning outcomes and student interest in learning at SMP-TQ Muadz bin Jabal Kendari on Pythagorean material. This is indicated by the level of completeness of student learning outcomes reaching 77% and student interest in learning is in the high category.